Prevalence and healthcare utilization in managing herpes zoster in primary care: a retrospective study in an Asian urban population - Chan, Xin-Bei Valerie; Tan, Ngiap Chuan; Ng, Mark Chung Wai; Ng, Ding Xuan; Koh, Yi Ling Eileen; Aau, Wai Keong; Ng, Chirk Jenn (Frontiers in Public Health, 2023)
Herpes zoster (HZ) causes significant morbidity, particularly in older adults. With the advent of a recombinant zoster vaccine, HZ is potentially preventable. However, data on HZ burden and healthcare utilization in primary care populations remains scarce. This study described the prevalence and healthcare utilization in managing HZ in a developed community. A retrospective database review was conducted across a cluster of 8 public primary care clinics in urban Singapore. Data of multi-ethnic Asian patients with a diagnosis code of 'herpes zoster' from 2018-2020 was extracted from their electronic medical records. Socio-demographic, clinical, visitation, medical leave, prescription, and referral data were analyzed. A total of 2,987 out of 737,868 individuals were diagnosed with HZ over three years. The mean age was 59.9 (SD+15.5) years; 49.2% were male; 78.5% Chinese, 12.2% Malay, and 4.1% Indian. The prevalence was 221, 224, 203 per 100,000 persons in 2018, 2019, and 2020 respectively. The 70-79-year age group had the highest prevalence (829/100,000) across three years. Oral acyclovir (median daily dose 4000mg; median duration 7 days) and topical acyclovir were prescribed in 71.6% and 47.6% respectively. Analgesia prescribed were gabapentin (41.0%), paracetamol combinations (30.1%), oral NSAIDs (23.7%), opioids (6.0%), and tricyclic antidepressants (1.9%). Most individuals consulted only once (84.3%); 32.7% of them required medical leave and 5.6% had more than 7 days of absenteeism. HZ-related referrals to the hospital were required in 8.9% (4.9% emergency, 2.8% ophthalmology). The findings of this study suggest a need for HZ vaccination among older age groups. Visitation and referral rates were low. The use of topical acyclovir was uncovered, and further research should evaluate the underlying reasons, benefits, and harms of such practice. The use of analgesia combinations may be explored further.